Effect of Previous Scorpion Bite on the Ecacy of IntrathecallyAdministered Bupivacaine in Subarachnoid Block - Ashwini Patel; Sonali Tripathi (International Journal of Medical Research and Review, 2021)
Aim: To study the efficacy of spinal anesthesia in patients with previous scorpion bites and patientswith no such history.Method: In this study, 40 patients were divided into two groups each of 20,patients with h/o scorpion bite (group -1), patients with no such history (group -2), scheduled forlower abdominal and lower limb surgeries, the subarachnoid block was given with 3.0 ml of injectionBupivacaine 0.5% heavy using 26 gauzes Quincke spinal needle. A blind observer recorded asensory block using a needle prick and a motor block using the Bromage scale.Result: Patients whohad previous scorpion bites (group -1) had a significant failure rate of spinal anesthesia compared tothe patient with no such history (group - 2). Our study shows how in the bite group, the onset andpeak effect of sensory and motor block is prolonged statistically significantly after exposure to ascorpion bite. It also depends on the number of exposures, as shown in table 4.Conclusion: In thisstudy, it was observed that the patients with scorpion bites had a significant failure rate of spinalanesthesia, suggesting probable resistance to the local anesthetic agents as observed in previoussimilar studies.